The Synthesis, Characterization Gd(Iii) Complex with Heptilmethyl- Ditiocarbamate and 2,9-Dimethyl Phenanthroline as Anti-Tuberculosis - Yunus, Muhammad Arham; Indah, Raya; Nurfiansyah, Nurfiansyah; Mimin , Septiani (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2023)
Mycobacterium tuberculosis is a bacterium that causes tuberculosis infection disease. The aim of this study was to produce complex compounds that have the ability to damage the cell wall of Mycobacterium tuberculosis. Gd(III)Heptylmethyldithiocarbamate 2,9-dimethyl phenanthroline complex was synthesised and characterised by reacting N-heptylmethylamine, carbondisulphide, 2,9-dimethyl phenanthroline and lanthanide group metal ion (Gadolinium) using in situ method. Characterisation was carried out using electrothermal melting point, conductometer, UV-Vis spectrophotometer, and FT-IR spectrophotometer. The resulting Gd(III)Heptylmethyldithiocarbamate 2,9-dimethyl phenanthroline complex was white in colour as much as 7.01%, conductivity 20 Ω-1 and melting point 208-210o C. Testing of complex compounds gave effective results as antibacterial Mycobacterium tuberculosis.